2016
DOI: 10.1177/0971890716637694
|View full text |Cite
|
Sign up to set email alerts
|

Pentagon Performance Model of Indian MFIs

Abstract: Microfinance institutions (MFIs) extend financial and related services to the poorest population with an ultimate objective of poverty alleviation. Microfinance industry has seen an impressive growth in the past decade, although debates have stirred in recent years regarding their role and impact on society. Excessive profit making by MFIs retarded the desired social impact, thus, providing evidence for mission drift from the social objective of poverty alleviation to profit generation. The mission drift was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Also, she did not find any substantial evidence suggesting that small loans imply a higher sustainability risk. Balammal et al (2016) found that legal status, the regulatory environment, the age of the MFI, number of employees, capital structure, and cost per client have a significant impact on MFI financial performance.…”
Section: Explanatory Variables Of Mfi Financial Performance and Outreachmentioning
confidence: 99%
“…Also, she did not find any substantial evidence suggesting that small loans imply a higher sustainability risk. Balammal et al (2016) found that legal status, the regulatory environment, the age of the MFI, number of employees, capital structure, and cost per client have a significant impact on MFI financial performance.…”
Section: Explanatory Variables Of Mfi Financial Performance and Outreachmentioning
confidence: 99%